Sol-gel assisted fabrication of collagen hydrolysate composite scaffold: a novel therapeutic alternative to the traditional collagen scaffold - Ramadass, Satiesh Kumar; Perumal, Sathiamurthi; Gopinath, Arun; Nisal, Anuya; Subramanian, Saravanan; Madhan, Balaraman (ACS Applied Materials & Interfaces, 2014)
Collagen is one of the most widely used biomaterial for various biomedical applications. In this Research Article, we present a novel approach of using collagen hydrolysate, smaller fragments of collagen, as an alternative to traditionally used collagen scaffold. Collagen hydrolysate composite scaffold (CHCS) was fabricated with sol-gel transition procedure using tetraethoxysilane as the silica precursor. CHCS exhibits porous morphology with pore sizes varying between 380 and 780 mu m. Incorporation of silica conferred CHCS with controlled biodegradation and better water uptake capacity. Notably, 3T3 fibroblast proliferation was seen to be significantly better under CHCS treatment when compared to treatment with collagen scaffold. Additionally, CHCS showed excellent antimicrobial activity against the wound pathogens Staphylococcus aureus, Bacillus subtilis, and Escherichia coli due to the inherited antimicrobial activity of collagen hydrolysate. In vivo wound healing experiments with full thickness excision wounds in rat model demonstrated that wounds treated with CHCS showed accelerated healing when compared to wounds treated with collagen scaffold. These findings indicate that the CHCS scaffold from collagen fragments would be an effective and affordable alternative to the traditionally used collagen structural biomaterials.
Keywords: collagen; collagen hydrolysate; scaffold; sol-gel; tissue engineering; wound Healing

Role of open source tools and resources in virtual screening for drug discovery - Karthikeyan, Muthukumarasamy; Vyas, Renu (Combinatorial Chemistry & High Throughput Screening, 2015)
Advancement in chemoinformatics research in parallel with availability of high performance computing platform has made handling of large scale multi-dimensional scientific data for high throughput drug discovery easier. In this study we have explored publicly available molecular databases with the help of open-source based integrated in-house molecular informatics tools for virtual screening. The virtual screening literature for past decade has been extensively investigated and thoroughly analyzed to reveal interesting patterns with respect to the drug, target, scaffold and disease space. The review also focuses on the integrated chemoinformatics tools that are capable of harvesting chemical data from textual literature information and transform them into truly computable chemical structures, identification of unique fragments and scaffolds from a class of compounds, automatic generation of focused virtual libraries, computation of molecular descriptors for structure-activity relationship studies, application of conventional filters used in lead discovery along with in-house developed exhaustive PTC (Pharmacophore, Toxicophores and Chemophores) filters and machine learning tools for the design of potential disease specific inhibitors. A case study on kinase inhibitors is provided as an example.
Keywords: Chemoinformatics; kinases; open source; scaffold; virtual screening

Electrospinning of non-ionic cellulose ethers/polyvinyl alcohol nanofibers: characterization and applications - Wali, Ashwini; Zhang, Yucheng; Sengupta, Poulomi; Higaki, Yuji; Takahara, Atsushi; Badiger, Manohar V. (Carbohydrate Polymers, 2018)
The morphology of spin-coated films and electrospun fibers of ethyl hydroxy ethyl cellulose (EHEC), hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) and their blends with Poly(vinyl alcohol) (PVA) was examined by AFM, SEM and contact angle measurements. These polysaccharides upon blending with PVA exhibited smooth surface which was evidenced by Atomic Force Microscopy (AFM) observation. The electrospinnability of above polysaccharides with PVA was demonstrated for the first time. The oriented fibers could be obtained using a rotating disc collector. Contact angles of spin-coated films and electrospun fibers were discussed in terms of hydrophobicity and wetting characteristics. Further, The nanofibers of EHEC/PVA were in-situ crosslinked using citric acid and were used for controlled release of an antibacterial drug, Chlorhexidine Digluconate (ChD). In-vitro studies of cytotoxicity, cell growth and cell proliferation were performed using L929 mouse fibroblast cells. These nanofiber mats show potential in drug delivery and as scaffolds in tissue engineering applications.
Keywords: cellulose; drug delivery; electrospinning; Ethyl hydroxy ethyl cellulose; Hydrophobically modified ethyl hydroxy ethyl; scaffold; Spin coating

Silk fibroin and ceramic scaffolds: comparative in vitro studies for bone regeneration - Deshpande, Rucha; Shukla, Swati; Sayyad, Raeesa; Salunke, Shalmali; Nisal, Anuya; Venugopalan, Premnath (Bioengineering & Translational Medicine, 2021)
Synthetic bone void fillers based on calcium ceramics are used to fill cavities in the bone and promote bone regeneration. More recently, silk fibroin (SF), a protein polymer obtained from Bombyx mori silkworm, has emerged as a promising material in bone void filling. In this work, we have compared the safety and efficacy of two types of silk fibroin-based bone void fillers with currently used and commercially available ceramic bone void fillers (based on calcium sulphate, beta tricalcium phosphate, and beta tricalcium phosphate with hydroxyapatite). Further, we have also evaluated these two types of SF scaffolds, which have strikingly different structural attributes. The biocompatibility of these scaffolds was comparable as assessed by cytotoxicity assay, cellular adhesion assay, and immunogenic assay. Ability of the scaffolds to support differentiation of human mesenchymal stem cells (hMSCs) into an osteoblastic lineage was also evaluated in an in vitro differentiation experiment using reverse transcriptase polymerase chain reaction analysis. These results revealed that cells cultured on SF scaffolds exhibit higher expression of early to late markers such as Runx2, BMPs, collagen, osterix, osteopontin, and osteocalcin as compared with ceramic-based scaffolds. This observation was further validated by studying the expression of alkaline phosphatase and calcium deposition. We also show that scaffolds made from same material of SF, but characterized by very different pore architectures, have diverse outcome in stem cell differentiation.
Keywords: beta tricalcium phosphate; bone regeneration; bone void filler; calcium sulphate; hMSCs; hydroxyapatite; osteoblasts; scaffold; Silk fibroin